Needs Analysis for Developing Communicative Speaking Materials for Tenth Grade Senior High School Students - Aulia Hafisa (Journal of English Language Teaching and Linguistics, 2026)
Although speaking is a key component of English language learning, many Indonesian EFL students still struggle to communicate effectively in English. Existing instructional materials often emphasize language knowledge rather than meaningful communication, creating a gap between classroom learning and real-life language use. This study aimed to analyze the speaking needs of tenth-grade EFL students at Senior High School 1 Petarukan, Indonesia, as a basis for developing communicative speaking materials. The research employed a descriptive design, combining quantitative and qualitative approaches. Hutchinson & Waters’ (1987) needs analysis framework served as the foundation of the study. Data were collected through questionnaires administered to 66 students and semi-structured interviews with their English teacher. The findings indicate that students prefer speaking materials that are communicative, contextual, and closely connected to their real-life experiences while also supporting their academic goals. They highlighted the importance of vocabulary enrichment, pronunciation practice, and opportunities to participate in authentic communicative activities. These findings provide valuable insights into learners’ speaking needs and offer a foundation for designing communicative speaking materials aligned with students’ proficiency levels, preferences, and classroom realities.